Lock-In Effects in Online Labor Markets - Fabrizio Ciotti; Lars Hornuf; Eliza Stenzhorn (Center for Economic Studies and ifo Institute (CESifo), 2021)
This article reports on an investigation of the role of lock-in exploitation and the impact of reputation portability on workers' switching behaviors in online labor markets. Online platforms using reputation mechanisms typically prevent users from transferring their ratings to other platforms, inducing lock-in effects and high switching costs and leaving users vulnerable to platform exploitation. With a theoretical model, in which workers in online labor markets are locked-in by their reputational data, we test the effects using an online lab-in-the-field decision experiment. In addition to comparing a policy regime with and without reputation portability, we vary lock-in exploitation using platform fees to consider how switching behavior might differ according to monetary motives and fairness preferences. Theoretically, this study reveals how reputational investments can produce switching costs that platforms can exploit. Experimentally, the results suggest that reputation portability mitigates lock-in effects, making users less susceptible to lock-in exploitation. The data further show that switching is driven primarily by monetary motives, but perceiving the fee as unfair also has a significant role.
Keywords: J24; D91; L51; 330; crowdsourcing; online markets; online labor; reputation portability; switching costs